Heterologous Expression of a Thermostable Chitinase from Myxococcus xanthus and Its Application for High Yield Production of Glucosamine from Shrimp Shell - Yongmei Lyu (MDPI AG, 2021)
Glucosamine (GlcN) is a widely used food supplement. Hence, enormous attention has been concerned with enzymatic production of GlcN owing to its advantage over a chemical approach. In this study, a previously unstudied chitinase gene (MxChi) in the genome of Myxococcus xanthus was cloned, expressed in recombinant soluble form and purified to homogeneity. TLC-, UPLC-, and microplate-reader- based activity tests confirmed MxChi hydrolyzes colloidal chitin to chitobiose as sole product. The optimal catalytic pH and temperature of MxChi was identified as 7.0 and 55 °C, respectively. MxChi exhibited 80% activity after 72 h incubation at 37 °C. The site-directed mutagenesis revealed that the amino acids D323A, D325A, and E327A of MxChi were in the DXDXE catalytic motif of GH18. When coupled with β-N-acetylhexosaminidase (SnHex) and deacetylase (CmCBDA), the enzyme allowed one-pot extraction of GlcN from colloidal chitin and shrimp shell. The optimal condition was 37 °C, pH 8.0, and 1/3/16.5 (MxChi/SnHex/CmCBDA), conducted by orthogonal design for the enzymatic cascades. Under this condition, the yield of GlcN was 26.33 mg from 400 mg shrimp shell. Facile recombinant in E. coli, robust thermostability and pure product herein makes newly discovered chitinase a valuable candidate for the green recycling of chitin rich waste.